Exosomal microRNA‐16‐5p from human urine‐derived stem cells ameliorates diabetic nephropathy through protection of podocyte - Duan, Yu‐Rui; Chen, Bao‐Ping; Chen, Fang; Yang, Su‐Xia; Zhu, Chao‐Yang; Ma, Ya‐Li; Li, Yang; Shi, Jun (Journal of cellular and molecular medicine, 2021)
Diabetic nephropathy (DN) remains one of the severe complications associated with diabetes mellitus. It is worthwhile to uncover the underlying mechanisms of clinical benefits of human urine‐derived stem cells (hUSCs) in the treatment of DN. At present, the clinical benefits associated with hUSCs in the treatment of DN remains unclear. Hence, our study aims to investigate protective effect of hUSC exosome along with microRNA‐16‐5p (miR‐16‐5p) on podocytes in DN via vascular endothelial growth factor A (VEGFA). Initially, miR‐16‐5p was predicated to target VEGFA based on data retrieved from several bioinformatics databases. Notably, dual‐luciferase report gene assay provided further verification confirming the prediction. Moreover, our results demonstrated that high glucose (HG) stimulation could inhibit miR‐16‐5p and promote VEGFA in human podocytes (HPDCs). miR‐16‐5p in hUSCs was transferred through the exosome pathway to HG‐treated HPDCs. The viability and apoptosis rate of podocytes after HG treatment together with expression of the related factors were subsequently determined. The results indicated that miR‐16‐5p secreted by hUSCs could improve podocyte injury induced by HG. In addition, VEGA silencing could also ameliorate HG‐induced podocyte injury. Finally, hUSC exosomes containing overexpressed miR‐16‐5p were injected into diabetic rats via tail vein, followed by qualification of miR‐16‐5p and observation on the changes of podocytes, which revealed that overexpressed miR‐16‐5p in hUSCs conferred protective effects on HPDCs in diabetic rats. Taken together, the present study revealed that overexpressed miR‐16‐5p in hUSC exosomes could protect HPDCs induced by HG and suppress VEGFA expression and podocytic apoptosis, providing fresh insights for novel treatment of DN.